Inside the Civano Project : a case study of large-scale sustainable neighborhood development - Nichols, C. Alan (McGraw-Hill's AccessEngineering., 2010)
This GreenSource book offers a complete survey of Civano, the largest high-performance mixed-use community in the United States. Located in Tucson, Arizona, Civano encompasses high standards of resource conservation, sustainability, and solar energy use. Inside the Civano Project features insider information on the planning, funding, building, and management of this development, which integrates residential communities with shopping, workplace, school, and civic facilities, as well as parks and natural open spaces. The book discusses the zoning and building code guidelines, sustainable building materials, energy standards, and water conservation technologies that make Civano ahead of its time. -- Publisher description.